Literature Review: Factors Influencing Contraceptive Choice Among Women of Childbearing Age - Asmarani, Sri Utami; Purwati, Ayu Endang; Dewi, Sri Wulan Ratna; Sandriani, Sandriani (INDOGENIUS, 2025)
Background & Objective: Family planning is an effort to regulate childbirth, including the spacing and ideal age of childbirth, as well as pregnancy, through promotion, protection, and assistance in accordance with reproductive rights, in order to realize a quality family. Therefore, family planning is a government program designed to balance population needs. Contraceptive use aims to fulfill reproductive rights, help people plan the number and timing of their children, and prevent unwanted pregnancies. Proper contraceptive use can reduce the risk of maternal and infant mortality. Therefore, ensuring access to quality family planning programs should be a priority in health services. The purpose of this literature review is to determine the factors that influence the selection of contraceptives in women of childbearing age. Method: The research method used is a literature review study that tries to explore information about the factors that influence the selection of contraceptives in women of childbearing age.The type of data used is secondary data. Sources for conducting this literature review include a systematic search study of computerized databases on Google Scholar in the form of research journals totaling 5 articles. The research journals used are from 2020 to 2024. Result: The results of the research analyzed by the researchers, from 5 journals, showed that the main factors influencing the selection of contraceptives were knowledge and husband support. While other factors that influence the selection of contraceptives are age, education, occupation and attitude. Conclusion: Increase education to husbands and always involve husbands in family planning counseling. So that husbands can provide appropriate support to their wives and can strengthen couple communication in making contraceptive decisions.